The Influence of Organization Culture and Work Motivation on Employee Productivity of Bank BJB Rancaekek Branch - Yudhy Yudhy; Nur’aeni Nur’aeni (Research Collaboration Community (RCC), 2020)
This study aimed to learn the influence of organization culture on employee productivity in Bank BJB Syariah Rancaekek Branch, and to know the influence of work motivation on employee productivity in Bank BJB Syariah Rancaekek Branch. The object of study is to know the organization culture at Bank BJB Syariah Rancaekek Branch. The type of study is associative quantitative, the type of data is primary data and use data collection techniques of observations, interviews, questionnaires and literature studies. Sampling technique is census technique with 18 respondents. The result of the study showed that there is significant influence between organization culture on employee productivity in Bank BJB Syariah Rancaekek Branch and organization culture on employee work motivation in Bank BJB Syariah Rancaekek Branch.